Problem opodatkowania „sumy pieniężnej” przyznanej w wyniku uwzględnienia skargi na przewlekłość postępowania - Goettel, Aleksy; Franusz, Anna (Kwartalnik Prawa Publicznego, 2012)
In spite of guarantees formulated in Article 6 of the European Convention for The Protection of Human Rights and Fundamental Freedoms and in Article 45 of the Constitution of the Republic of Poland, the parties’ right to have their case heard within reasonable time before a court or in preparatory proceedings supervised by public prosecutor, had not always been observed. Therefore in 2004 the Parliament adopted the special Act which allows the parties to lodge with the court a complaint concerning the excessive length. One of the legal instrument to reduce the violation of the right to a hearing within reasonable time is the obligation for the courts to grant the complainant the certain amount of money (between PLN 2,000 and PLN 20,000) as a just satisfaction. Unfortunately it has not been established in Polish legal doctrine whether granted benefit cause tax consequences, including tax liability. Personal Income Tax is levied on all kinds of income, except for income exempt from taxation like compensation for damage or indemnity for moral injury granted by the courts. Nevertheless taxation of the granted ‘amount of money’ has been disputable. On one hand the provisions of the statue do not mention ‘the amount of money’ granted by a court as an example of tax exemption, on the other hand its legal nature has been controversial. In authors’ opinion ‘the amount of money’ is sui generis indemnity for moral injury, therefore it undoubtedly should be exempted for Personal Income Tax. The study presents the conclusions referring to correct interpretation of the provisions concerning the exemptions from Personal Income Tax. It also includes recommendations for the Polish legislator to improve controversial and therefore unjust for tax payers, provisions.